Do planejamento à implementação: adotando uma ferramenta Open Source em um ambiente corporativo - Kazimirski, Cristian (2024)
This article describes how network monitoring in companies can be a significant challenge, often characterized by a lack of adequate oversight, resulting in performance issues and frequent failures. To address this situation, the open-source tool Zabbix was implemented, standing out for its robustness and flexibility. The main results achieved with the use of Zabbix include notable improvements in service availability, proactive problem detection, and resource optimization, enabling the identification and resolution of issues that previously went unnoticed. This approach not only enhanced operational efficiency but also prepared the infrastructure for future demands.